Associations between ergogenic supplement use and eating behaviors among university students. Issue 6 (2nd November 2021) - Nagata, Jason M.; Peebles, Rebecka; Hill, Katherine B.; Gorrell, Sasha; Carlson, Jennifer L.
ABSTRACT: Ergogenic supplements to improve athletic performance are commonly used among college athletes, but little is known about their association with eating disorder symptoms. The objective of this study was to examine associations between ergogenic supplement use and disordered eating attitudes and behaviors among university students, and to compare differences by sex. Undergraduate students from 10 top-ranked National College Athletics Association (NCAA) Division I colleges completed an online survey on supplement use, athletic activities, and eating attitudes and behaviors. Among 1633 university students, males (38.9%) reported higher rates of current supplement use than females (15.2%) ( p < .001). In linear regression models adjusting for athletic status and body mass index, current supplement use was associated with higher Eating Disorders Examination-Questionnaire (EDE-Q) Global, Shape Concern, and Restraint scores in both males and females. Supplement use was associated with driven/compelled exercise (OR 2.00, 95% CI 1.33–2.99) in males and diuretic (OR 6.39, 95% CI 2.02–20.22) and diet pill use (OR 3.07, 95% CI 1.79–5.27) in females. Results suggest ergogenic supplement use is common in undergraduates and associated with disordered eating attitudes and behaviors. Clinicians should screen for disordered eating behaviors particularly in young adults who use ergogenic supplements.